Biologics and severe asthma in children. Issue 2 (24th April 2023) - Saxena, Shikha; Rosas-Salazar, Christian; Fitzpatrick, Anne; Bacharier, Leonard B.
Abstract : Purpose of review: Severe asthma can carry significant morbidity and mortality for patients, and it places a burden on families and the healthcare system. Biologic agents have revolutionized the care of patients with severe asthma in recent years. Evidence surrounding some of these therapies is limited in the pediatric population, but recent studies show that they significantly improve asthma care when used appropriately. In this review, we discuss the biologic therapies currently approved to treat severe asthma in school-age children and adolescents. Recent findings: Randomized controlled trials have been published in support of biologics in children and/or adolescents. These therapies have been shown to reduce the annual rate of severe asthma exacerbations by at least 40–50%, and some up to about 70%. Improvements in asthma control, lung function, oral corticosteroid use, and quality of life have also been demonstrated, although these vary by agent. Furthermore, these therapies have reassuring safety profiles in pediatric patients. Summary: With three biologic agents approved for children ages 6–11 years and five approved for adolescents ages >12 years, it can be challenging to select one. The therapy should be chosen after careful consideration of the patient's asthma phenotype and biomarkers. Additional pediatric-specific clinical trials would be helpful in developing evidence-based guidelines on biologic therapies in this population.